(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تساعد دراسة تغير طيف طاقة اكستون فان- موت التعرف على بنية العديد من الجمل المتعددة الطبقات، وكذلك دراسة الرقائق الفائقة. وإن إيجادEex طيف طاقة اكستون فان – موت (Wannier-Mott exciton) في طبقة رقيقة لنصف ناقل من جملة مكونة من ثلاث طبقات، بدلالة معامل لاتناحي( انزوتروبية) العازلية الكهربائية، و سماكة الطبقة. يبين أن تغير في المجال من 0 إلى 1 يسمح بتغيرEex في المجال ، وقد وُجدَ أن زيادة يؤدي إلى تناقص Eex. The study on the energy spectrum of W-Mott exciton helps us to identify the structure of thin multilayer system and super films. This paper aims to find the energy spectrum of W-Mott exciton in the thin semiconductor layer of system consisting of three layers as a function of anisotrpic dielectric constant, and the . .thickness The variation of in the range (0-1) leads to change Eex during the matrix .Increase leads to decreasing of Eex.